Feasibility of Random Forest and Multivariate Adaptive Regression Splines for Predicting Long-Term Mean Monthly Dew Point Temperature - Zhang, Guodao; Bateni, Sayed M.; Jun, Changhyun; Khoshkam, Helaleh; Band, Shahab S.; Mosavi, Amir (Frontiers in Environmental Science, 2022)
The accurate estimation of the dew point temperature (Tdew) is important in climatological, agricultural, and agronomical studies. In this study, the feasibility of two soft computing methods, random forest (RF) and multivariate adaptive regression splines (MARS), is evaluated for predicting the long-term mean monthly Tdew. Various weather variables including air temperature, sunshine duration, relative humidity, and incoming solar radiation, etc. from 50 weather stations in Iran as well as their geographical information (or a subset of them) are used in RF and MARS as inputs. Three statistical indicators namely, root mean square error (RMSE), mean absolute error (MAE), and correlation coefficient (R) are used to assess the accuracy of Tdew estimates from both models for different input configurations. The results demonstrate the capability of the RF and MARS methods for predicting the long-term mean monthly Tdew. The combined scenarios in both the RF and MARS methods are found to produce the best Tdew estimates. The best Tdew estimates of were observed obtained by the MARS model with the RMSE, MAE, and R of respectively 0.17 °C, 0.14 °C, and 1.000 in the training phase; 0.15 °C, 0.12 °C, and 1.000 in the validation phase; and 0.18 °C, 0.14 °C, and 0.999 in the testing phase.